75.3k views
11 votes
Can someone please help me anyoneeeee

Can someone please help me anyoneeeee-example-1

1 Answer

2 votes

Answer:

(8, 0)

Explanation:

TAKE NOTE: In a glide reflection, you always start w/ the second transformation.

STEP 1: (2, 7) affected by the reflection

RULE (in this case): (x, y) --> (y, x)

(2, 7) => (7, 2)

STEP 2: (7, 2) affected by the translation

RULE: (x, y) --> (x + horizontal shift, y + vertical shift)

(7, 2) => (7+1, 2-2) or (8, 0)

You can check your answer by doing this the opposite way.

Hope this helped ^^

(Please inform me of any mistakes or misunderstandings!]

User Charles
by
5.5k points